2010
DOI: 10.1007/s10637-010-9481-8
|View full text |Cite
|
Sign up to set email alerts
|

The anti-cancer activity of dihydroartemisinin is associated with induction of iron-dependent endoplasmic reticulum stress in colorectal carcinoma HCT116 cells

Abstract: Dihydroartemisinin (DHA), the main active metabolite of artemisinin derivatives, is among the artemisinin derivatives possessing potent anti-malarial and anti-cancer activities. In the present study, we found that DHA displayed significant anti-proliferative activity in human colorectal carcinoma HCT116 cells, which may be attributed to its induction of G1 phase arrest and apoptosis. To further elucidate the mechanism of action of DHA, a proteomic study employed two-dimensional gel electrophoresis (2-DE) and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
80
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 36 publications
2
80
0
Order By: Relevance
“…Since ER stress can be caused by oxidative stress, the iron-mediated endoperoxide cleavages of DHA result in the unbalance of redox to induce ER stress. 5 To response to ER stress, the translation of ATF4 mRNAs selectively increases, which induces the expression of genes involved in restoring ER homeostasis. 36 Among the ATF4 target genes, CHOP is one of the most induced, which is common considered as a mediator of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since ER stress can be caused by oxidative stress, the iron-mediated endoperoxide cleavages of DHA result in the unbalance of redox to induce ER stress. 5 To response to ER stress, the translation of ATF4 mRNAs selectively increases, which induces the expression of genes involved in restoring ER homeostasis. 36 Among the ATF4 target genes, CHOP is one of the most induced, which is common considered as a mediator of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…21 In addition, ER stress has proved to be one of the inducers of autophagy. 22 Interestingly, DHA induced-ER stress has been observed in several tumor cells, 23,24 and our previous studies have demonstrated that DHA both induce apoptosis and autophagy in various cancer cells. 25,26 The Complex relationships among ER stress, autophagy and apoptosis remain unclear, but it's perhaps noteworthy that we found p8 is involved in all of these 3 biological functions induced by DHA.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…In addition, the type of derivative was proved to target G 1 phase of the cell cycle [41] . Thus far, antitumor activity of artemisinins and the underlying mechanisms have been www.nature.com/aps Li Y Acta Pharmacologica Sinica npg widely studied [43][44][45][46][47][48][49] , however, few clinical trials were reported. Antimalarial chloroquine was used as immunosuppressive agent.…”
mentioning
confidence: 99%